2021
DOI: 10.4103/jomfp.jomfp_198_21
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and oral implications

Abstract: The emerging (COVID-19) pandemic is a global health disaster, caused by infection with severe acute respiratory syndrome coronavirus-2. The disease spreads at an alarming rate all over the world and presents a range of disease manifestations including asymptomatic, mild, moderate and severe symptoms irrespective of age groups. Most patients with severe symptoms exhibit underlying comorbidities such as diabetes, hypertension and obesity. Alternatively, there is an existing evidence for an association between or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
9

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
4
0
9
Order By: Relevance
“…45 Several studies have demonstrated the exacerbation of periodontal diseases in patients with chronic or severe systemic diseases; similar mechanisms of developing chronic and acute vascular reactions in the periodontal tissues have been observed in patients with some noninfectious and infectious diseases. [46][47][48] Indeed, in patients with coronavirus disease 2019 (COVID-19), a cytokine storm and thromboembolic complications were observed. 46 Such complications cause alterations in the oral cavity immune response and result in a severe course of periodontitis; a similar immune response is observed in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…45 Several studies have demonstrated the exacerbation of periodontal diseases in patients with chronic or severe systemic diseases; similar mechanisms of developing chronic and acute vascular reactions in the periodontal tissues have been observed in patients with some noninfectious and infectious diseases. [46][47][48] Indeed, in patients with coronavirus disease 2019 (COVID-19), a cytokine storm and thromboembolic complications were observed. 46 Such complications cause alterations in the oral cavity immune response and result in a severe course of periodontitis; a similar immune response is observed in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…al., Brazilian Journal of Health Review, Curitiba, v. 5, n. 6, p.22443-22457, nov./dec., 2022 2021). É importante lembrar, que se pode observar, ainda, alterações na mucosa oral que são frutos de associações com infecções fúngicas oportunistas como a candidíase ou a xerostomia (BOYAPATI et. al., 2021).…”
Section: Etiopatogênese Da Covid-19 E Suas Manifestações Oraisunclassified
“…Acrescenta-se ainda, um importante aspecto a ser avaliado pelo cirurgião dentista nesses pacientes: os fatores retentivos de biofilme, como a presença de alterações na anatomia periodontal, pelo aumento da profundidade da bolsa ou bolsas intraósseas e envolvimentos de furca, restaurações mal concluídas ou deterioradas, aparelhos fixos como os ortodônticos, infecções endodônticas e alterações patológicas (BOYAPATI et al, 2021). O dorso da língua também é considerado um nicho de microorganismos orais, onde a microflora dominante é Prevotella Veillonella, associados a um risco aumentado de morte por pneumonia em pacientes idosos imunocomprometidos (BAO, L. et al, 2020).…”
Section: Higiene Bucal Em Pacientes Submetidos à Ventilação Mecânicaunclassified
“…Individuals with COVID-19 frequently experience oral symptoms such altered taste and smell, mouth ulcers, gingival pain, and bleeding [ 8 ]. The angiotensin-converting enzyme 2 (ACE2) receptor, which is a target of SARS CoV-2, has already been proved to be expressed in gingival epithelial cells, tongue taste cells, and salivary glands [ 9 ]. As a result, the oral cavity, sensitive to SARS-CoV-2, is regarded to be a possible area for human-to-human viral transmissions.…”
Section: Introductionmentioning
confidence: 99%